Kaidah-Kaidah Khusus Siyasah Qadhaiyyah - Ghina Aulia Rizky; Muhammad Afriza Rifandy; Muhammad Ferdy Hasan; Lisnawati Lisnawati (STIKes Ibnu Sina Ajibarang, 2025)
Qawāʿid fiqhiyyah are a set of legal maxims or principles used in the science of fiqh to understand and interpret Islamic law. The term “qawāʿid” means rules or principles, while “fiqh” refers to a deep understanding of Islamic law. Thus, qawāʿid fiqhiyyah function as general guidelines in deriving legal conclusions from sharia texts. This study specifically examines the application of qawāʿid fiqhiyyah in the context of siyāsah fiqhiyyah, or Islamic political jurisprudence. Siyāsah fiqhiyyah refers to the principles of Islamic law applied in political and governmental affairs. In this context, “siyasah” refers to the management of public and state matters based on Islamic legal values. The main objective of applying these principles is to ensure that governmental policies and actions align with sharia and aim at achieving the welfare (maṣlaḥah) of the people. This research aims to explore how legal maxims play a role in shaping a normative framework for public policy within an Islamic governance context. Using a qualitative approach and literature review, the analysis shows that the integration of qawāʿid fiqhiyyah and siyāsah fiqhiyyah is essential in establishing a just government that adheres to Islamic principles and promotes public welfare. The findings are expected to contribute to the body of knowledge in Islamic legal studies, particularly in offering contextual solutions for the challenges of modern governance.